2009
DOI: 10.1083/jcb.200909003
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of cell migration: a multiscale tuning model

Abstract: Cell migration underlies tissue formation, maintenance, and regeneration as well as pathological conditions such as cancer invasion. Structural and molecular determinants of both tissue environment and cell behavior define whether cells migrate individually (through amoeboid or mesenchymal modes) or collectively. Using a multiparameter tuning model, we describe how dimension, density, stiffness, and orientation of the extracellular matrix together with cell determinants—including cell–cell and cell–matrix adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
989
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,187 publications
(1,031 citation statements)
references
References 90 publications
(180 reference statements)
29
989
2
11
Order By: Relevance
“…Rac GTPase activity critically regulates pseudopodial protrusions and mesenchymal cell migration in 3D gels (Sanz-Moreno et al, 2008;Friedl and Wolf, 2010), separately confirmed in the cell lines used in the present study by the use of dominant-negative Rac. Downstream from Rac, Arp2/3 initiates short-branched actin filaments that push against the cell membrane, leading to membrane protrusion.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Rac GTPase activity critically regulates pseudopodial protrusions and mesenchymal cell migration in 3D gels (Sanz-Moreno et al, 2008;Friedl and Wolf, 2010), separately confirmed in the cell lines used in the present study by the use of dominant-negative Rac. Downstream from Rac, Arp2/3 initiates short-branched actin filaments that push against the cell membrane, leading to membrane protrusion.…”
Section: Discussionsupporting
confidence: 74%
“…Tm5NM1-mediated changes to cell morphology and Src kinase activity A characteristic feature of mesenchymal migration in 3D cultures is the extension of long membrane processes in the direction of migration (as in Figure 1a), referred to as pseudopodia (Friedl and Wolf, 2010). We observed that the majority of the cells overexpressing Tm5NM1 failed to extend pseudopodia.…”
Section: Tm5nm1 Inhibits Mesenchymal Migrationmentioning
confidence: 72%
See 1 more Smart Citation
“…b1 integrin is a well established player in cell motility (Friedl et al, 2004;Cordes and Park, 2007;Caswell et al, 2009;Friedl and Wolf, 2010). In this study, we show that its silencing, as well its inhibition, affects the invasive properties of A549 cells, both in terms of directional migration through Transwells and b1 integrin controls EGFR signaling V Morello et al in the ability to invade into 3D matrix.…”
Section: Discussionmentioning
confidence: 52%
“…2.2. Such forces are assumed to be viscous (Allena and Aubry 2012;Friedl and Wolf 2010;Phillipson et al 2006;Sakamoto et al 2011) and may be distinguished into a frontal (f f ) and a rear (f r ) force as follows:…”
Section: Intra-synchronizationmentioning
confidence: 99%